THE DETERMINANTS OF GREEN PURCHASING BEHAVIOR - Rahayu Lestari; Resti Hardini; Melati; Kumba Digdowiseiso; Safiek Mokhlis (RADJA PUBLIKA, 2024)
The objective of this study is to identify and analyze the factors that influence Green Purchasing Behavior, specifically in relation to environmentally friendly products and services. The research background emphasizes the intricate nature of the various factors that impact consumers' choices when selecting environmentally friendly products. These factors include environmental consciousness, knowledge about green products, perception of price, and brand reputation. The research methodology employs a systematic approach of conducting a literature review to gather and analyze findings from diverse sources of relevant scientific literature published between the years 2020 and 2024. The research findings indicate that environmental consciousness and familiarity with eco-friendly products are crucial determinants in shaping Green Purchasing Behavior. Consumer purchasing decisions are significantly influenced by price perception, brand image, and the availability of green products in the market. Nevertheless, the intricate interconnections among these factors underscore the significance of adopting a comprehensive approach when developing successful marketing and education strategies. Green Purchasing Behavior can be effectively stimulated through education on green products, implementation of transparent pricing strategies, and cultivation of a positive brand image. The research findings underscore the importance of collaboration among producers, sellers, government, and society in establishing favorable conditions that promote sustainable consumer choices. These findings offer valuable insights for future research, policy makers, and marketing managers in devising more efficient strategies to promote the adoption of environmentally sustainable consumption patterns.